Determinants and acceptability of HIV self-testing among vulnerable groups in sub-Saharan Africa: A scoping review protocol - Olanrewaju Oladimeji; Felix Emeka Anyiam; Maureen Nokuthula Sibiya (BMJ Open)
Introduction HIV self-testing (HIVST) is where individuals collect their specimens and perform the HIV test privately. HIVST has improved testing uptake and coverage, especially among vulnerable groups of sub-Saharan Africa (SSA). Vulnerable groups include key populations such as men who have sex with men, sex workers, people who inject drugs, lesbian, gay, bisexual and transgender persons and young women. However, little is known about the determinants and acceptability of HIVST among these groups in SSA. Therefore, this scoping review aims to explore the determinants and acceptability of HIVST among vulnerable groups in SSA.Methods A scoping review will be conducted using the Arksey and O’Malley framework and further refined by Levac framework. The review will follow a six-step approach: (1) identifying the research question, (2) identifying relevant studies, (3) study selection eligibility, (4) charting the data, (5) collating, summarising and reporting the results and (6) consultation. A comprehensive search strategy will be developed, and the following electronic databases will be searched: MEDLINE, Embase, Global Health and the Cochrane Library. Grey literature will also be searched, including conference abstracts and reports. Eligibility criteria will include studies conducted in SSA, published between 2010 and 2023, focusing on vulnerable groups and exploring the determinants and acceptability of HIVST. Two independent reviewers will screen identified studies’ titles, abstracts and full texts. Any disagreements will be resolved through discussion or consultation with a third reviewer. Data extraction will be conducted using a standardised form.Ethics and dissemination This review, not requiring ethical approval, aims to inform policy and intervention design to boost HIV testing adoption within vulnerable communities. We plan to disseminate our findings via a peer-reviewed journal, policy briefs, conference presentations and stakeholder engagement.